It’s the Antigen Stupid:: A Risk/Reward Approach to the Problem of Orphan Drug Act Exclusivity for Monoclonal Antibody Therapeutics - Bohrer, Robert A. (Science and Technology Law Review, 2004)
The Orphan Drug Act of 1983 is an attempt at solving an important problem: how to induce a market-driven pharmaceutical industry to develop new therapeutics for diseases affecting relatively small numbers of persons. In the case of protein therapeutics produced by biotechnology, the FDA’s administration of the Act has repeatedly led to litigation and controversy. The principal and recurrent problem has been determining when a second applicant for the approval of a drug to treat an orphan disease (or “indication”) is seeking approval for the “same” drug as a previously approved orphan drug. The problem is how to provide sufficient protection for pioneering orphan drugs to stimulate the development of new drugs for smaller patient populations, while not so broadly protecting orphan drugs as to preclude additional therapeutics that make new contributions to the treatment of those diseases. In the context of antibody therapeutics, that problem is somewhat different than for other protein therapeutics. For antibodies, it is the antigen that will primarily determine the antibody’s efficacy, and it is the proof that an antigen is clinically useful in the treatment of a disease that provides the biggest risk in antibody development. The approach to orphan drug exclusivity recommended here is that the FDA presume antibodies to the same antigen, of the same immunoglobin class and with the same mechanism of action to be the same drug unless the second antibody is shown to be clinically superior to the first.